(untitled) (Western Journal of Medical and Biomedical Sciences, 2025)
Renal involvement in sickle cell disease (SCD) is common and often develops silently in early stages. Traditional markers such as proteinuria, serum creatinine and estimated glomerular filtration rate (eGFR) may not detect early renal damage. The renal resistivity index (RRI), derived from Doppler ultrasonography, offers a non-invasive means of identifying early intrarenal haemodynamic changes. The main aim was to evaluate renal resistivity index and its relationship with proteinuria and eGFR in patients with SCD attending a Nigerian tertiary health facility. It was a crosssectional descriptive study was conducted among 313 individuals with confirmed SCD. Participants underwent renal Doppler ultrasonography to measure RRI, urinalysis and eGFR was calculated using serum creatinine. Clinical data, including blood transfusion, bone pain crises, and hospitalisations in the past year, were recorded. Associations were analysed using logistic regression, with statistical significance set at p < 0.05. The results are as follows: Of the participants, 67.1% had elevated RRI (≥0.7), while 11.0% had reduced eGFR (<60 mL/min/1.73 m²). An inverse but non-significant correlation was observed between RRI and eGFR (r = –0.14, p = 0.812). A significant association was found between elevated RRI and history of blood transfusion in the past year (OR = 1.682; 95% CI: 1.005–2.816; p = 0.047). No significant associations were observed between RRI and bone pain crises, hospitalisation, or proteinuria. In conclusion, Elevated RRI is common in SCD patients and may reflect early renal vascular changes not detectable by eGFR alone. Its association with blood transfusion suggests that RRI may serve as an early marker of disease severity. Renal Doppler ultrasonography could be integrated into routine monitoring of SCD patients for early detection of nephropathy.